2018
DOI: 10.1590/1414-431x20176426
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of serum microRNA expression in male workers with occupational noise-induced hearing loss

Abstract: Occupational noise-induced hearing loss (ONIHL) is a prevalent occupational disorder that impairs auditory function in workers exposed to prolonged noise. However, serum microRNA expression in ONIHL subjects has not yet been studied. We aimed to compare the serum microRNA expression profiles in male workers of ONIHL subjects and controls. MicroRNA microarray analysis revealed that four serum microRNAs were differentially expressed between controls (n=3) and ONIHL subjects (n=3). Among these microRNAs, three we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
0
17
0
2
Order By: Relevance
“…MiR-1275 was involved in IGF-signaling by directly targeting IGFbinding proteins in hepatocellular and squamous cell carcinoma 45,46 while miR-1229-5p contributed to the pathogenesis of occupational noise-induced hearing loss by repressing MAPK1 signaling. 47 MiR-4459 altered stemness maintenance in human embryonic stem cells 48 and miR-199b-5p, highly conserved among species, was so far mostly studied in cancer cells. Among other targets, the Notch-response gene HES1 49 and HIF1a 50 were proposed as target genes for miR-199b-5p.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-1275 was involved in IGF-signaling by directly targeting IGFbinding proteins in hepatocellular and squamous cell carcinoma 45,46 while miR-1229-5p contributed to the pathogenesis of occupational noise-induced hearing loss by repressing MAPK1 signaling. 47 MiR-4459 altered stemness maintenance in human embryonic stem cells 48 and miR-199b-5p, highly conserved among species, was so far mostly studied in cancer cells. Among other targets, the Notch-response gene HES1 49 and HIF1a 50 were proposed as target genes for miR-199b-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, studies on miRNAs and hearing loss have demonstrated that these miRNAs can be used as potential biomarkers to indicate NIHL [15,23]. In a study involving miRNA-15a-1 and miRNA-18a in the development of the ear structure of zebrafish, it was found that the number of hair cells in the deformed body decreased, and the inner ear structure was abnormal [24].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the control group, the expression of miRNA-24, miRNA-185-5p, and miRNA-451a increased significantly in the NIHL group [14]. Li et al [15] reported that the serum miRNA-1229-5p level of male workers suffering from NIHL was significantly higher than the control group.…”
Section: Introductionmentioning
confidence: 95%
“…Maybe these miRNAs do not be expressed in the mitochondria of spermatozoa, or their expression is very low. The miR‐4484 has been showed a putative marker in lymphoma (Tamaddon, Geramizadeh, Karimi, Mowla, & Abroun, ), glioblastoma (Nawaz et al, ), cervical squamous cell carcinoma (Chen et al, ) and breast cancer (Tamaddon et al, ) and in occupational noise‐induced hearing loss (Li et al, ). Previous studies showed the role of miR‐4463 overexpression in inhibiting aberrant vascular smooth muscle cell (VSMC) migration(Wang et al, ), enhancing H 2 O 2 induced oxidative stress and apoptosis (Wang, He, Deng, He, & Zhou, ), novel biomarker in arteriosclerosis obliterans (He et al, ) and polycystic ovary syndrome (Ding et al, ).…”
Section: Discussionmentioning
confidence: 99%